If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (V + -1)(V + 8) = 0 Reorder the terms: (-1 + V)(V + 8) = 0 Reorder the terms: (-1 + V)(8 + V) = 0 Multiply (-1 + V) * (8 + V) (-1(8 + V) + V(8 + V)) = 0 ((8 * -1 + V * -1) + V(8 + V)) = 0 ((-8 + -1V) + V(8 + V)) = 0 (-8 + -1V + (8 * V + V * V)) = 0 (-8 + -1V + (8V + V2)) = 0 Combine like terms: -1V + 8V = 7V (-8 + 7V + V2) = 0 Solving -8 + 7V + V2 = 0 Solving for variable 'V'. Factor a trinomial. (-8 + -1V)(1 + -1V) = 0Subproblem 1
Set the factor '(-8 + -1V)' equal to zero and attempt to solve: Simplifying -8 + -1V = 0 Solving -8 + -1V = 0 Move all terms containing V to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -1V = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -1V = 0 + 8 -1V = 0 + 8 Combine like terms: 0 + 8 = 8 -1V = 8 Divide each side by '-1'. V = -8 Simplifying V = -8Subproblem 2
Set the factor '(1 + -1V)' equal to zero and attempt to solve: Simplifying 1 + -1V = 0 Solving 1 + -1V = 0 Move all terms containing V to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1V = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1V = 0 + -1 -1V = 0 + -1 Combine like terms: 0 + -1 = -1 -1V = -1 Divide each side by '-1'. V = 1 Simplifying V = 1Solution
V = {-8, 1}
| (8y)9/y= | | f(0)=6x^2+7x-6 | | 2x-4=mx | | G(X)=80*4+150 | | (8y)9/y | | y=(x^2)-8 | | F(X)=110*5 | | 8c+3(5-c)=10 | | 4z+30=7z | | F(X)=110X | | 36x-12=8x+15 | | X/3-b=9 | | w^2-5w-8=0 | | x^2-5w-8=0 | | 2/3k=112/9 | | 2sin^2x=7sinx-5 | | 17+3y=88 | | 12(3)-3y=15 | | 4x+2y=58.80 | | 10x+3162+15x=3237 | | 9-(4-7*8)= | | X+(.2*X)=75.6 | | 20=100e^8y | | 4y-19=17 | | 5x/4-3/4=7/4 | | 67/2a-15 | | y=100e^8x | | (18)2+(x)2=(x+14) | | 21/.75 | | 7x^2+10=9 | | 5(x-4)=-3(x+2)+33 | | 0=x^2+14-45 |